A CQR Study of the Fishing for Wellness Nature-Based Group Intervention for Adults Facing Adversity. Issue 2 (3rd April 2022) - Reese, Ryan F.; DeMeyer, Melisa; Hoag, Amy; Glass, Lauren; Madigan, Chris; Avent Harris, Janeé
ABSTRACT: We examined participant experiences of the 7-week Fishing for Wellness (FFW) nature-based group counseling protocol. Eleven white adult male and female clients aged 27–73 years ( M = 47.8, SD = 14.3) completed semi-structured interviews in exploring contextual factors impacting participation, self-reported change, and possible elements within FFW contributing to that change. Data were analyzed using consensual qualitative research. Participants reported expanded self-awareness, self-efficacy, connection with self and others, and nature relatedness two to three months following the group's termination. Findings lend initial support for applying the FFW protocol when working with clients presenting with adverse life experiences.